Analysis of the Quality of Fresh and Used Cooking Oil Among Fried Catfish Street Vendors in the Eastern Region of Lamongan Sub-District, Lamongan District - Azzury, Novita Mizzalluna; Yulistiani, Ratna (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
Cooking oil that is repeatedly used by vendors can cause damage and a decline in quality. Moreover, it can pose health risks. Repeated use of cooking oil leads to various degradation reactions such as oxidation, hydrolysis, and polymerization. This research aims to analyze the quality differences between initial and used cooking oil. The study is a survey with a cross-sectional study method. The sampling technique used purposive sampling (13 vendors) with data analysis using a paired t-test at a 5% significance level. Cooking oil samples were taken twice a day. The chemical quality analysis results of 13 initial cooking oil samples showed that the percentage that did not meet SNI 7709:2019 standards for water content was 46.15%, free fatty acids were 46.15%, and peroxide values were 69.23%. For used cooking oil samples, the percentages that did not meet SNI 7709:2019 standards for water content were 92.30%, free fatty acids were 100%, and peroxide values were 100%. The average TBA value for all initial-use cooking oil samples was 0.44 mg MDA/kg, and for used cooking oil samples was 0.65 mg MDA/kg, both higher than the reference sample (0.15 mg MDA/kg).. The t-test results showed that there were quality differences between the initial and used cooking oil used by street vendors selling pecel lele in the eastern region of Lamongan District.